INFECTION EVENTS IN MULTIPLE MYELOMA DURING THE EARLY PERIOD OF AUTOLOGOUS STEM CELL TRANSPLANTATION - Shirkhan Amikishiyev; Sevgi Kalayoğlu Beşışık; İpek Yönal Hindilerden; Mustafa Nuri Yenerel; Arif Atahan Çağatay; Simge Erdem; Gülkan Özkan; Meliha Nalçacı (İstanbul Tıp Fakültesi Dergisi)
Objective: Multiple myeloma (MM) patients have a high risk of developing infections. In this study, we documented the infec tion events in patients with MM who underwent autologous hae matopoietic stem cell transplantation (AHSCT).Material and Method: Patients who received an induction regi men and underwent AHSCT were enrolled in the study. Routine antimicrobial prophylaxis was not given. Infection treatment was performed in accordance with the febrile neutropenia guidelines.Result: Between May 2007 and November 2016, 150 patients with MM underwent AHSCT. The median age was 51.7±7.2 years, and the male-to-female ratio was 84/66. Nearly all patients developed fever. The median time from the HSCT day to the first fever episode was 7.4±2.8 days. Pneumonia and oropharyngeal candidiasis were frequently associated with fever. Blood and urine culture positivity was 18.6% and 20%, respectively. The neutropenia duration was not associated with culture positivity but proved to be longer in patients who had received two types of induction regimen (8.4±3.7 vs. 7.4±2.3 days, p=0.056). The mortality rate in the first 100 days was 0.6%, which was similar to the results of other experienced centers.Conclusion: Our study encompassed the period when the in duction regimen included combinations of chemotherapy, and novel agents were used after chemotherapy refractoriness or for improvement in response quality. In relation to this, mostpatients received second-line induction therapy. The infection events were manageable, and patients showed acceptable out comes and a very low early mortality rate.